Non-coding RNA in cancer - Yan, Huiwen; Bu, Pengcheng (Essays in biochemistry, 2021)
Majority of the human genome is transcribed to RNAs that do not encode proteins. These non-coding RNAs (ncRNAs) play crucial roles in regulating the initiation and progression of various cancers. Given the importance of the ncRNAs, the roles of ncRNAs in cancers have been reviewed elsewhere. Thus, in this review, we mainly focus on the recent studies of the function, regulatory mechanism and therapeutic potential of the ncRNAs including microRNA (miRNA), long ncRNA (lncRNA), circular RNA (circRNA) and PIWI interacting RNA (piRNA), in different type of cancers.